Cardiovascular Ultrasound Contrast Agent and Microembolic Signals on Transcranial Doppler. Issue 4 (December 2018) - Moore, Anne; Nguyen, Winnie; Reynolds, Drew; Kim, Louis; Sekhar, Laligam; Longstreth, W. T.
Transcranial Doppler (TCD) monitoring of the intracranial vessels is useful for the detection of microembolic signals (MES), which can help with risk stratification and evaluation of therapies. The presence of any emboli during a TCD exam is concerning and treatment is controversial. In this case, an unusual high count of emboli were detected in all vessels, which prompted a change in clinical management. It is now believed that the injectable cardiovascular ultrasound contrast agent (Definity®) was the cause of the large number of MES. Ramanathan reported a similar case in which an unusual amount of MES were detected during emboli monitoring (EM) and were felt to be contamination from Definity® contrast injected 2 hours prior to the EM exam. When unexpectedly faced with numerous MES, practitioners should consider other factors that can influence the results of TCD with EM.